The Evaluation of Marketing Service Management at SMAN 2 Penukal Utara PALI - Robi Yanto; Zainal Berlian; Ahmad Zainuri (The Future of Education Journal, 2024)
This study evaluates the marketing service management at SMAN 2 Penukal Utara PALI, South Sumatra, to understand the effectiveness of the strategies implemented to attract prospective students and build a positive image of the school. The research approach used is descriptive qualitative, with data collected through interviews, observations, and document analysis. The findings of the study indicate that although there have been significant efforts in the implementation of marketing strategies, there are still shortcomings in promotion, facilities, and communication between the school and the community. The recommendations provided include the development of facilities, diversification of extracurricular activities, strengthening the positive image, and implementing more aggressive marketing strategies. The results of this evaluation are expected to help SMAN 2 Penukal Utara PALI improve its competitiveness and become a leading educational institution in the region.